2021
DOI: 10.1186/s12863-021-01002-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polymorphisms of SLC22A7, NGFR, ARNTL and PPP2R2B genes and Milk production traits in Chinese Holstein

Abstract: Background Our preliminary work confirmed that, SLC22A7 (solute carrier family 22 member 7), NGFR (nerve growth factor receptor), ARNTL (aryl hydrocarbon receptor nuclear translocator like) and PPP2R2B (protein phosphatase 2 regulatory subunit Bβ) genes were differentially expressed in dairy cows during different stages of lactation, and involved in the lipid metabolism through insulin, PI3K-Akt, MAPK, AMPK, mTOR, and PPAR signaling pathways, so we considered these four genes as the candidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…As the most complex trait in dairy cow production, milk production trait is regulated by many genes and environmental factors. Some nucleotide polymorphisms may be caused by a large (Fu et al, 2022;Jia et al, 2021;Potu et al, 2022) have discussed that SNPs in milk production candidate functional genes can significantly affect milk production traits of dairy cows. In addition, by adding functional gene information of target traits with large genetic effects to expand SNP marker data, the accuracy of genome breeding value prediction can be improved (de Las et al, 2020;Ye et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most complex trait in dairy cow production, milk production trait is regulated by many genes and environmental factors. Some nucleotide polymorphisms may be caused by a large (Fu et al, 2022;Jia et al, 2021;Potu et al, 2022) have discussed that SNPs in milk production candidate functional genes can significantly affect milk production traits of dairy cows. In addition, by adding functional gene information of target traits with large genetic effects to expand SNP marker data, the accuracy of genome breeding value prediction can be improved (de Las et al, 2020;Ye et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evaluation of population genetic structure can provide reference for genetic evaluation, protection and utilization of high‐quality resource populations of Holstein. At present, a large number of studies (Fu et al., 2022; Jia et al., 2021; Potu et al., 2022) have discussed that SNPs in milk production candidate functional genes can significantly affect milk production traits of dairy cows. In addition, by adding functional gene information of target traits with large genetic effects to expand SNP marker data, the accuracy of genome breeding value prediction can be improved (de Las et al., 2020; Ye et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For the GL trait, a number of candidate genes located within 20 kb of genome-wide significant and suggestive significant SNPs were identified in both lines. Among them, the PPP2R2B gene had a genetic significant effect on milk production traits in Chinese Holstein [ 67 ]. This gene may be associated with sperm motility in Duroc pigs as a candidate gene [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many researchers try to find the key genes/loci that have significant impacts on milk production traits through candidate gene analysis, genome-wide association analysis and omics data analysis strategies ( Schennink et al, 2009 ; Canovas et al, 2013 ; Cui et al, 2014 ; Liang et al, 2017 ; Bhat et al, 2020 ). Studies have shown that the milk production traits of dairy cows can be significantly affected by SNPs in the genes ( Jiang et al, 2010 ; Dux et al, 2018 ; Han et al, 2019a ; Han et al, 2019b ; Clancey et al, 2019 ; Jia et al, 2021 ; Du et al, 2022 ; Fu et al, 2022 ; Ye et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%